2004
DOI: 10.1111/j.1365-2141.2004.04992.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of paroxysmal nocturnal haemoglobinuria using modern diagnostic assays

Abstract: Summary Paroxysmal nocturnal haemoglobinuria (PNH) is an uncommon, acquired disorder of blood cells caused by mutation of the phosphatidylinositol glycan class A (PIG‐A) gene. The disease often manifests with haemoglobinuria, peripheral blood cytopenias, and venous thrombosis. The natural history of PNH has been documented in retrospective series; but there has only been one study that correlated the more sensitive and specific flow cytometric assays that have become available in the last decade with severe sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
202
0
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(223 citation statements)
references
References 24 publications
4
202
0
13
Order By: Relevance
“…27 Through logistical regression, Moyo et al calculated the increase in odds ratio for thrombosis to be 1.64 for each 10% increase in the proportion of PNH cells. 24 These findings correlate with other studies which have shown that the occurrence of thrombosis is noticeably elevated in PNH patients with a proportion of PNH cells as low as 10% when compared to normal population controls.…”
Section: Clinical Presentationsupporting
confidence: 81%
See 3 more Smart Citations
“…27 Through logistical regression, Moyo et al calculated the increase in odds ratio for thrombosis to be 1.64 for each 10% increase in the proportion of PNH cells. 24 These findings correlate with other studies which have shown that the occurrence of thrombosis is noticeably elevated in PNH patients with a proportion of PNH cells as low as 10% when compared to normal population controls.…”
Section: Clinical Presentationsupporting
confidence: 81%
“…The mean proportion of PNH granulocytes in patients with these symptoms was at least twice that of patients who did not possess these clinical manifestations. 24 As previously described, thrombosis is the most serious complication associated with PNH. Thrombotic events are reported to be of venous origin in 85% of cases, arterial in 15% of cases and involve more than one site at the same time in 20.5% of cases.…”
Section: Clinical Presentationmentioning
confidence: 94%
See 2 more Smart Citations
“…(15). Two large studies have shown that in all patients with thrombosis, the PNH clone in granulocytes was greater than 50% and 61% respectively (15,16). However, in some studies, PNH clones have been reported at much lower levels in patients with thrombosis.…”
Section: Discussionmentioning
confidence: 99%